Postprocedural LGE‐CMR comparison of laser and radiofrequency ablation lesions after pulmonary vein isolation - Figueras i Ventura, Rosa M.; Mǎrgulescu, Andrei D.; Benito, Eva M.; Alarcón, Francisco; Enomoto, Norihiro; Prat‐Gonzalez, Susanna; Perea, Rosario J.; Borràs, Roger; Chipa, Fredy; Arbelo, Elena; Tolosana, Jose M.; Brugada, Josep; et al. (Journal of cardiovascular electrophysiology, 2018)
Introduction The purpose of this study was to compare the anatomical characteristics of scar formation achieved by visual‐guided laser balloon (Laser) and radiofrequency (RF) pulmonary vein isolation (PVI), using late‐gadolinium‐enhanced cardiac magnetic resonance imaging (LGE‐CMR). Methods and results We included 17 patients with paroxysmal or early persistent drug resistant AF who underwent Laser ablation; 2 were excluded due to procedure‐related complications. The sample was matched with a historical group of 15 patients who underwent PVI using RF. LGE‐CMR sequences were acquired before and 3 months post‐PVI. Ablation gaps were defined as pulmonary vein (PV) perimeter sections showing no gadolinium enhancement. The number of ablation gaps was lower in Laser versus RF ablations (median 7 vs. 14, P  =  0.015). Complete anatomical PVI (circumferential scar around PV, without gaps) was more frequently achieved with Laser than with RF (39% vs. 19% of PVs, P  =  0.025). Fewer gaps were present at the superior and anterior left PV and posterior right PV antral regions in the Laser group, compared to RF. Scar extension into the PVs was similar in both groups, although RF produced more extensive ablation scar toward the LA body. AF recurrences at 1 year were similar in both groups (Laser 36% vs. RF 27%, P  =  1.00). Conclusions Compared to RF, Laser ablation achieved more complete anatomical PVI, with less LA scar extension. However, AF recurrence appears to be similar after Laser compared to RF ablation. Further studies are needed to assess whether the anatomical advantages of Laser ablation translate into clinical benefit in patients with AF.